Effect of argon-oxygen ratio on dielectric and energy storage properties of Ba(Zr0.35Ti0.65)O3 thin films. Issue 20 (15th October 2022) - Li, Xiang; Sun, Zheng; Sun, Yanji; Yue, Xipeng; Han, Yemei; Xie, Yangyang; Hu, Kai; Wang, Fang; Zhang, Kailiang
Abstract: Lead-free Ba(Zr0.35 Ti0.65 )O3 (short as BZT35) ferroelectric thin films are prepared by RF magnetron sputtering on Pt/Ti/SiO2 /Si substrates. Effects of argon-to-oxygen (short as Ar/O2 ) ratios on phase transition, dielectric and energy storage properties are studied. The research found that all thin films are perovskite structures. With the decrease of Ar/O2, the oxygen vacancies (OVs) in the film are effectively suppressed, which promotes the film to obtain a larger dielectric constant, smaller dielectric loss, and lower leakage current density. The BZT35 film prepared under Ar/O2 = 40:10 has excellent energy storage density (48.03 J/cm 3 ) and efficiency (87.7%) because of its elongated hysteresis loop, the largest polarization difference (ΔP = 22.91 μC/cm 2 ), higher breakdown field strength (Eb = 4.50 MV/cm) and lower leakage current density (J = 2.3 × 10 −5 A/cm 2 ) and high power density of 7.94 MW/cm 3 . In addition, the BZT35 film also has excellent frequency stability (500 Hz-20 kHz). These excellent properties show that BZT35 has very broad application prospects in energy storage.